An Analysis of Student’s Speaking Anxiety and its Effect on Speaking Performance - Cucu Sutarsyah (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2017)
This study was carried out to seek if there is a negative psychological factor known as anxiety could really affect students’ speaking performance and to find the difference in speaking performance between students with higher level of anxiety and students with lower level of anxiety and also to seek which of the factors of anxiety is dominant. The participants of this research were the first year students of SMPN 2 Bandar Lampung. There were 27 students in that class. The research design was ex post facto to seek the correlation between the variables. Questionnaire and speaking test were used as data collection and then they were analyzed by using Independent T-Test and Linear Regression to test the hypotheses. The results show that the students’ speaking performance significantly differs between the two groups. The mean score of higher level of anxiety students was 62.37 while the mean score for lower level of anxiety students was 83.81. Based on the analysis by using Mann-Whitney U Test, it shows that lower level anxiety students have higher score in speaking performance than those with higher level of anxiety as the computation resulted in p value at 0.005. The next analysis by using Linear Regression resulted in r2 (0.319). The data show that speaking anxiety may give negative contribution to the overall students’ speaking performance achievement. It also found that nervousness is dominant factor followed by worry and tension.